2017
DOI: 10.1039/c7ra03885b
|View full text |Cite
|
Sign up to set email alerts
|

Y-doped V2O5 with enhanced lithium storage performance

Abstract: Y-doped V2O5 shows greatly enhanced cycling stability, better rate capability, and a higher Li+ diffusion coefficient than the pure V2O5 counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…By comparison, the potential separation of the ternary Fe 2 O 3 /Fe 3 O 4 /FeCO 3 composite is smaller than that of single-component Fe 2 O 3 under the same scan rate, suggesting its superior electrochemical reaction reversibility. The Li + diffusion coefficients ( D Li + ) of the two samples are calculated by using Randles–Sevcik equation , where I p is the peak current (A), n is the number of electrons involved in oxidation or reduction, A is the electrode area (cm 2 ), D Li + is the diffusion coefficient of Li + (cm 2 s –1 ), C Li + is the shuttle concentration (mol cm –3 ), and v is the scan rate (V s –1 ) in CV measurement. Based on the CV data (Figure c,d), we can obtain four lines ( I p vs v 1/2 ) as shown in Figure e,f.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, the potential separation of the ternary Fe 2 O 3 /Fe 3 O 4 /FeCO 3 composite is smaller than that of single-component Fe 2 O 3 under the same scan rate, suggesting its superior electrochemical reaction reversibility. The Li + diffusion coefficients ( D Li + ) of the two samples are calculated by using Randles–Sevcik equation , where I p is the peak current (A), n is the number of electrons involved in oxidation or reduction, A is the electrode area (cm 2 ), D Li + is the diffusion coefficient of Li + (cm 2 s –1 ), C Li + is the shuttle concentration (mol cm –3 ), and v is the scan rate (V s –1 ) in CV measurement. Based on the CV data (Figure c,d), we can obtain four lines ( I p vs v 1/2 ) as shown in Figure e,f.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, vanadium bronzes of the general stoichiometry MxV2O5 (M = Na, Nb, Ta, K, Cu, Ag) were investigated for their capacitive performance in terms of current density, reversibility, ion storage capacity, and cyclic stability [32]. In [64], it was shown that dopant cations enhance the structural stability of V2O5 and, consequently, improve electrochemical performance. FE-SEM was carried out to study the effect of substrate temperature on the morphology of V2O5 coatings for 5%, 10%, and 15% Ag loading at a temperature of 400 °C for a growth period of 1 h (Figure 2).…”
Section: Electrochemical Performance Of V2o5 Based On Aqueous LI Elecmentioning
confidence: 99%
“…[36][37][38] Therefore, this may generate a Marangoni flow travelling towards the area with a higher interfacial tension (cathodic pole) to drag the liquid metal toward the cathode. [39] As such, liquid metal can be succeedfully separated from the solid shell. We observed the separation of liquid metal from the solid shell ≈40 s after applying the voltage (Figure 1f), and the liquid metal droplet immediately actuated toward the anode similar to the behaviors of bare Galinstan droplets.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%